Primary Determinants of PLS Financing in Islamic Banks: Empirical Insights from Indonesia (Ekonomi Syariah IAIN Kudus, 2025)
This study aims to identify the factors that influence Profit-Loss Sharing (PLS) Financing in Islamic Banking in Indonesia. This study uses Islamic bank financial performance instrument variables, which consist of Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Third Party Funds (DPK), and macroeconomic variables, namely the World Uncertainty Index (WUI), Industrial Production Index (IPI), and BI-Rate monetary variables. This study uses data from January 2015 to May 2024. The research used is a quantitative method with the Auto-Regressive Distributed Lag (ARDL) analysis model. The findings of this study indicate that NPF and BI-Rate variables have a significant effect on PLS financing in the short and long term. Meanwhile, the variables of CAR, DPK, WUI, and IPI do not have a significant effect in the short and long term. The results of this study are expected to serve as recommendations for the government and stakeholders in formulating and establishing appropriate policies and strategies for Islamic banking.